2005
DOI: 10.1039/b416598e
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium(iii) adsorption: a soft and simple method to prevent TiO2deactivation during salicylic acid photodegradation

Abstract: Deposition of poisoning species on TiO2 during salicylic acid photodegradation can be halted when Al(III) has been previously adsorbed on the catalyst surface; this widens the application of photocatalysis to more concentrated solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Surface Fe 3+ cations enhanced maleic acid photooxidation [1455] [1458]. Adsorbed Al 3+ cations diminished the build-up of strongly bound surface intermediates that inhibited salicylic acid photodecomposition on TiO 2 [1459]. In a slightly different sense, addition of Fe 3+ to the surface of A was shown to inhibit formation of surface sites that can initiating the A-to-R phase transformation [1458].…”
Section: Metal Cationsmentioning
confidence: 95%
“…Surface Fe 3+ cations enhanced maleic acid photooxidation [1455] [1458]. Adsorbed Al 3+ cations diminished the build-up of strongly bound surface intermediates that inhibited salicylic acid photodecomposition on TiO 2 [1459]. In a slightly different sense, addition of Fe 3+ to the surface of A was shown to inhibit formation of surface sites that can initiating the A-to-R phase transformation [1458].…”
Section: Metal Cationsmentioning
confidence: 95%
“…It has been suggested that cations of small radii and low valence accelerate the transition to rutile owing to the increase in oxygen vacancies that result from the assumed substitution of Ti 4? ions with cations of lower valences [43,109,157,164,165]. Charge neutrality thus requires an increase in the level of oxygen vacancies and/or the formation of Ti interstitials of lower valence [82,172].…”
Section: Cationic Dopantsmentioning
confidence: 99%
“…• Reduction of the band gap in titania [18,151] • Introduction of mid-gap states [56,163] • Improvement in charge carrier separation [68,73] • Increase in the levels of surface-adsorbed species (e.g., hydroxyl radicals) [43] It often is not appreciated that all titania is contaminated with some levels of impurities. The presence of unintentional impurities or intentional dopants has a strong effect on the kinetics of the anatase to rutile transition [170].…”
Section: Dopant Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could limit the application of photocatalysis to high ionic strength media, like seawater [78]. However, adsorbed Al 3+ cations halted poisoning caused by adsorption of strongly bound surface intermediates on TiO 2 during salicylic acid photodegradation [79]. In anatase/water systems under bandgap irradiation, both the organic substrate (formate) oxidation initiated by photogenerated valence band holes and the formation of hydrogen peroxide from O 2 reduction (by conduction band electrons) are strongly influenced by the presence of Zn 2+ cations [80].…”
Section: Adsorption Of Cationsmentioning
confidence: 97%